(3QaY GdedGeI YeG bjd aj GdMLGeIs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3EdG bGdhG Ydjc HGdMLGeI abd deG PcQ Hf GdLhRi s
(3BNQgG (B:s
(3GdHGH GdKGdK GdYdGeI EHQGgje s
(3fSNI ecQQI ef GdeNWhW Qbe (B710 s
(3hdcfgG HgG NQes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs